ISLAM AND MUSLIM LIFE IN WESTREN COUNTRIES: THE AUSTRALIAN EXPERIENCE - Syaie, Akhmad Najibul Khairi; Dzahabi, Muhammad Yaqzan Ershad; Fajar, Abbas Sofwan Matlail (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
This article delves into the intricate relationship between Islam and Western societies, focusing on Australia’s unique experience. Historically and contemporarily, this relationship has been marked by both interaction and tension. In secular Western nations like Australia, the growing presence of Islam has heightened concerns and Islamophobia, particularly post-9/11. This article examines how Muslims in Australia, many of whom are immigrants, practice Islam differently compared to their counterparts in majority-Muslim countries. The history of Islam in Australia traces back to the 16th century with Makassar fishermen and continued with Afghan and Indian settlers in the 19th century. Despite Australia’s multicultural policies, Muslims often face discrimination and negative stereotypes, exacerbated by government policies and media portrayals that link Islam with extremism. The impact of the September 11 attacks significantly altered Western perceptions of Islam, associating it with terrorism and influencing Australian policies. As a result, Muslims in Australia struggle to balance their religious identity with societal integration, frequently encountering racism and marginalization, despite their substantial contributions to the nation’s cultural diversity.